2014
DOI: 10.1212/wnl.0000000000000188
|View full text |Cite
|
Sign up to set email alerts
|

Neuroimaging abnormalities in adults with sickle cell anemia

Abstract: Objective: This study was conducted to determine the relationship of frontal lobe cortical thickness and basal ganglia volumes to measures of cognition in adults with sickle cell anemia (SCA).Methods: Participants included 120 adults with SCA with no history of neurologic dysfunction and 33 healthy controls (HCs). Participants were enrolled at 12 medical center sites, and raters were blinded to diagnostic group. We hypothesized that individuals with SCA would exhibit reductions in frontal lobe cortex thickness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
85
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(91 citation statements)
references
References 36 publications
4
85
1
1
Order By: Relevance
“…35,37 Furthermore, deficits in processing speed are also detectable in pediatric populations across multiple studies and similarly correlate with the burden of cerebrovascular damage. 8,9,38 Thus, it can be hypothesized that this domain may be particularly susceptible to brain aging in SCD, although direct comparisons between pediatric and adult populations are complicated by the heterogeneity of the study populations and tests used.…”
Section: Discussionmentioning
confidence: 99%
“…35,37 Furthermore, deficits in processing speed are also detectable in pediatric populations across multiple studies and similarly correlate with the burden of cerebrovascular damage. 8,9,38 Thus, it can be hypothesized that this domain may be particularly susceptible to brain aging in SCD, although direct comparisons between pediatric and adult populations are complicated by the heterogeneity of the study populations and tests used.…”
Section: Discussionmentioning
confidence: 99%
“…A voxel-based morphometry study showed decreased white matter density in the arterial borderzone distribution corresponding to disease severity, 16 and smaller gray matter volume was found in children with no evidence of SCI but low IQ. 17 There is evidence of cortical thinning in the frontal lobes 18 and posterior medial surfaces of both hemispheres, 19 and volumetric deficits of subcortical structures. 20 In those patients with SCA without SCI, a complete picture of the extent of white matter injury is still unclear.…”
Section: July 2015mentioning
confidence: 99%
“…cerebral blood flow 36 and basal ganglia volume 18 and may also be associated with white matter integrity.…”
Section: Strokementioning
confidence: 99%
“…However, similar kinds of neurocognitive outcomes have been reported in children and adults with sickle cell anemia who have experienced overt stroke, silent cerebral infarcts, and localized abnormalities detected using segmental analysis on MRI. 4,5 In sickle cell anemia, vasculopathy, endothelial dysfunction, hypoxia, and poor oxygen perfusion are all mechanisms associated with neurocognitive impairment independent of evidence of specific white matter or other CNS structural injury. 6 It is, therefore, not surprising that similar patterns of neurocognitive function following CRT might be related to CMBs and that the neurocognitive outcomes observed are similar to those in diseases with primary CNS vasculopathy.…”
mentioning
confidence: 99%